Narrativeas a Historical and Pedagogical Source and its Representation in the Space of the Museum - Oleksiy Karamanov; Mariya Vasylyshyn (Pedagogical Discourse, 2013)
The narrative as an important historical and educational source for human experience collecting and accumulating in the space of the museum is analysed. The main types of narratives and their characteristics are defined. The possibility to applying narrative as part of oral history, which is an organic way of filling the content of historical events, objects and events in the space of the museum is proved. Special attention is paid to the«storytelling»technology which promotes the inclusion of new information presented in the form of stories in the process of learning.